Estudo crítico do discurso de acórdãos judiciais sobre o sistema de cotas raciais nas universidades - Andrade, Patrícia Ricardo (2021)
In this research we intend to analyze the discourses of judges in the Appellate Court level on lawsuits involving the racial quotas in Brazilian Universities. We aim to understand the evolution of the applicability of anti-racist actions and the consequences of implementing this public policy in legal system since the sentence of Minister Ricardo Lewandowski, in 2012, together with other laws that endorse the affirmative action policy for blacks. The research corpus resulted from the compilation of sample of 96 decisions obtained through internet research, reaching the number of five judicial judgments arising from the five Federal Regional Courts of Brazil, issued from the year of 2012, after the STF decision on the constitutionality of racial quotas. The present research followed the qualitative method and we used Teun van Dijk categories to analyze the corpora regarding the socio-cognitive context (2012a; 2012b) and the racist and anti-racist discourse (2012a, 2012b, 2012c, 2014, 2016) to observe the aspects sociocognitive, global organization or argumentative scheme and local discursive strategies, in decisions in the complicated second of the legal domain. The analysis includes precedentes and non precedente legal actions the judges, most in favor of the common rules in the Public Notice of the event by the Universities, which is hegemonic also in the sample of 96 decisions. There was a greater tendency for legal discourses to include, in the judgments, the current laws and arguments on quota policy, result that did not confirm the research hypothesis. Thus, positive developments for the anti-racist groups in the actions occurred since 2012, because with the establishment, without Brazilian law, of arguments of the legal scope favorable to the applicability of the affirmative policy by the STF, the decisions taken to consider these discourses as a reference, even though racial conflicts are that the legal institution expresses and regulates selected far from becoming resolved and consensual.